Potential Liquefaction of Loose Sand Lenses: Case Study In Surabaya East Coastal Plain, Indonesia - Agung, Putera Agung M.; Anjang Ahmad, Mustaffa (International Journal of Integrated Engineering, 2014)
The zone of east coastal Surabaya becomes the object of development for the city, especially to the east coastal plain. Although in the recent years, that area does not have a structure or heavy construction and or a high rise building yet, but in the future the zone will turn into a business area with a variety of activities.. The zone of east coastal Surabaya is an alluvium deposit area. This layer is considered as clay deposited from some rivers and sea. From general information, the typical soil stratigraphy consists of soft clay and silt layers with many sand lenses with or without coarse grained soil with a depth varying from 0.00 to 10.00 meters (m). The saturated sand lenses with a water table depth varies from 0.40 to 1.20 m is susceptible earthquake and it has a relatively large seismic amplification from base-rock due to geological and soil condition nature of the site. Liquefaction hazard of the sand lenses has to be anticipated and evaluated. For development of Surabaya city area toward the east coastal plain, all developer are recommended to give some criteria of sand lenses density and some consideration for anticipating the liquefaction hazard.